Simulation of trimmed flight of a helicopter using the URANS solver ANSYS fluent - Stalewski, W.; Pulfer, M.; Hirsch, F. (My University, 2019)
The methodology of simulation of a fully trimmed flight of rotorcraft has been developed and applied to simulate a helicopter flight within a range of flight velocities from a hover to fast flight at advance ratio 0.34. The presented approach is based on a solution of Unsteady Reynolds-Averaged Navier-Stokes (URANS) equations. In contrast to typical solutions of such problem, in the newly developed methodology, the flight controls corresponding to the trimmed-flight conditions are also determined based on the solution of URANS equations. The methodology is based on coupling of several computational models of Computational Fluid Dynamics and Flight Dynamic. The URANS equations are solved in a three-dimensional region surrounding the flying helicopter, using the ANSYS FLUENT code. The approach is truly three-dimensional, with truly modelled geometry and kinematics of main and tail rotor blades. This applies to modelling of blade flapping, too. The trimming procedure uses six independent parameters (i.e. collective and cyclic pitch of main rotor blades, collective pitch of tail rotor blades, pitch and bank angles of a helicopter) that should be adjusted so as to balance all forces and moments acting on the helicopter. The detailed description of the developed methodology as well as the results of simulation of trimmed hover of the helicopter are presented.